Implementasi Face Recognition Pada Aplikasi Desktop Untuk Rekam Kehadiran Siswa Menggunakan Metode Prototype (Studi Kasus: SMP Negeri 1 Cijambe) - Pramana Putra, Fajri; Dwi Aryadi, Indra; Pratama, Prayoga; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Student attendance recording is an important component in education, especially to ensure the efficiency and discipline of school management. The manual attendance system at SMPN 1 Cijambe often experiences problems in terms of time efficiency, data manipulation, and recording errors. The purpose of this research is to use artificial intelligence (AI) technology to create an attendance system that uses facial recognition. This device uses a camera to scan faces to record student attendance automatically and instantly. The implementation of this system showed improvements in time efficiency, recording accuracy, and integration with other administrative data, including student discipline records and grades. However, the research also pointed out issues in terms of infrastructure requirements, facial recognition accuracy, and biometric data security. It is hoped that the findings from this study will offer a new approach to the problem of manual attendance and serve as a template for the creation of comparable systems in other educational institutions.